Clinical Profile and Outcome of Patients with Dengue Syndrome in Hospital Care (Journal of Medicine, 2011)
Dengue is a viral febrile illness, which has become a major international public health concern including Bangladesh, spectrum of illness ranging from dengue fever (DF) to life threatening dengue haemorrhagic fever (DHF), dengue shock syndrome (DSS) and ultimately death. The clinical profiling and outcome during epidemic dengue outbreak was observed in Dhaka Medical College Hospital in 2000 to 2001. One hundred and fifty patients were systematically observed. Male female ratio was 5:1 with severity of illness in younger patients. Hundred percent patients had fever with 83% having generalized weakness. The severe cases(DHF) were having sudden sustained temperature of 103 degree farenheight. Majority have abdominal symptoms(>80%) while 10% had respiratory only. Sixty percent have hepatomegaly while 40 % spleenomealy while 80% of DHF had ascites. Above 75% cases of Dengue haemorhagic fever had positive tourniquet test while melaena was the commonest mucosal bleeds. No fatality was observed in this study although variability of discharge was seen in different groups. Keyword: Clinical, Profile, Outcome, Dengue, Hospital DOI: http://dx.doi.org/10.3329/jom.v12i2.6733 JOM 2011; 12(2): 131-138